2015
DOI: 10.1186/s12936-015-0841-x
|View full text |Cite
|
Sign up to set email alerts
|

Where have all the mosquito nets gone? Spatial modelling reveals mosquito net distributions across Tanzania do not target optimal Anopheles mosquito habitats

Abstract: BackgroundMalaria remains the deadliest vector-borne disease despite long-term, costly control efforts. The United Republic of Tanzania has implemented countrywide anti-malarial interventions over more than a decade, including national insecticide-treated net (ITN) rollouts and subsequent monitoring. While previous analyses have compared spatial variation in malaria endemicity with ITN distributions, no study has yet compared Anopheles habitat suitability to determine proper allocation of ITNs. This study asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…Regional factors seem to have an impact on the epidemiology of parasitic diseases, which can be attributed to geographical location and climatic conditions [36,37]. The altitude of Maoxian, Lixian and Ma'erkang was higher than that of other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Regional factors seem to have an impact on the epidemiology of parasitic diseases, which can be attributed to geographical location and climatic conditions [36,37]. The altitude of Maoxian, Lixian and Ma'erkang was higher than that of other areas.…”
Section: Discussionmentioning
confidence: 99%
“…It would be a mistake to see the current study as definitive, as one major limitation was that our findings did not include information to support or reject macroecological patterns related to parasite distribution. It is well understood that spatial distribution of parasites is influenced by abiotic and biotic environments, such as temperature, precipitation, altitude, presence of predators, human disturbance, geographic barriers, soil type and vegetation among other factors [36] [37]. In fact, previous studies suggest that biotic factors will be more relevant at a species equatorial range limit; whereas abiotic factors will influence the high latitude or poleward limit [21].…”
Section: Discussionmentioning
confidence: 99%
“…The role of vector control interventions could not be directly evaluated in the models due to data limitations; available data on LLIN coverage reflect only a limited geographic sample from prior targeted studies, which are conducted at different time points, or from national surveys designed to estimate district- or regional-level LLIN coverage indices (50), which biases finer-scale analyses. Nonetheless, previous studies in this region of northern Tanzania have found similar rates of bednet ownership in villages situated at low (750 m) and mid-altitudes (1,050 m) (51), therefore, the impact of interventions would likely be similar across the study area.…”
Section: Discussionmentioning
confidence: 99%